Atroposelective Synthesis of Isoriccardin C through a C−H Activated Heck Type Macrocyclization. Issue 9 (29th January 2021) - Marx, Lisa; Lamberty, Daniel; Choppin, Sabine; Colobert, Françoise; Speicher, Andreas
Abstract: Macrocyclization is typically the key step in syntheses of cyclophane‐type natural products. Considering compounds with axially chiral biaryl moieties, the control of atroposelectivity is essential for biological activity and is synthetically challenging. Herein we report on atroposelective macrocyclization involving an oxidative Heck type process and enabling the first atropo‐enantiopure synthesis of isoriccardin C. A chiral sulfinyl auxiliary in the ortho‐position of a biaryl axis (still flexible) was used to induce a C−H activated atropodiastereoselective oxidative Heck coupling (>98 % de). The traceless character of the sulfinyl auxiliary enables the introduction of a hydroxy group to give the target molecule with >98 % ee as well. Abstract : A chiral sulfinyl auxiliary group in ortho ‐position of a biaryl axis is directing in the adjacent aryl moiety an atropo‐diastereoselective ortho' ‐Fujiwara‐Moritani Heck coupling with dynamic kinetic resolution and can finally be transformed into a hydroxyl function of a natural occurring cyclophane type bisbibenzyl.